CAMPUR KODE SEBAGAI SUMBER KONFLIK BAHASA DI BAGIAN KOMENTAR INSTAGRAM - Reza Angriyashati Adara; Tin Hartini; Euis Nurhalizah (Institut Bisnis Muhammadiyah Bekasi, 2022)
Language conflict can happen anywhere, including on social media. Understanding language conflict may help to escalate problems that might arise in the aftermath. The present study aims to analyze language conflicts in social media comments. In order to obtain the results, the present study uses a descriptive qualitative method by analyzing 20 comments from three different posts on Instagram, a social media website. The findings of the present study suggest that language conflicts in Instagram’s comments might be caused by dictions used by the commenters. Their dictions can be interpreted differently by other commenters. In addition, code-mixing can cause language conflicts among commenters. As the commenter used a mix of Indonesian and English language due to their lack of knowledge in expressing their thoughts in the same language, it can cause a language conflict in Instagram’s comment section. The results of the present study suggest that language conflicts might arise due to a lack of knowledge regarding both languages. In order to avoid language conflicts, it seems important for concerned parties such as educational institutions and media to provide suitable promotion of the proper use of language and proper etiquette of social media